The Causality Variables of Financial Sector Deepening to Economic Growth in Indonesia 1986 - 2015 - Pramesti Widiya Astuti (Economics Development Analysis Journal, 2018)
This study aims to examine the causality and role as the variables of the financial sector deepening with economic growth in Indonesia. The test of causality in this research acres using heading Granger Causality Test and VECM test. The tests are conducted using annual data from 1986 to 2015. The result of research using heading Granger Causality shows that there is no causality between M2 ratio with economic growth. While the ratio of private credit by deposit money banks and gross fixed capital formation ratio has a one-way causality with economic growth. The ratio of total outstanding international debt securities with economic growth has bidirectional causality. Based on the results of VECM in the long run, the ratio of private credit by deposit money bank has a negative effect on economic growth and the ratio of total outstanding international debt securities has negative effect and not significant on GDP.